Treatment seeking for gambling disorder in nationwide register data – observations around a major shift in legislation - Håkansson, Anders; Karlsson, Anna; Widinghoff, Carolina (Frontiers in Public Health, 2024)
Background Treatment seeking for gambling disorder is known to be low and there has been a lack of longitudinal research regarding treatment opportunities. The present study aimed to assess possible changes in treatment uptake after a formal introduction of gambling disorder in social services and health care legislations, by using register data, including patient characteristics with respect to socio-demographics and comorbidities. Methods Nationwide register data were collected for the years 2005–2019, describing diagnoses in specialized out-patient health care and in in-patient hospital care. Numbers and characteristics of patients with gambling disorder were followed longitudinally. Also, a new legislation for treatment by public institutions was introduced in 2018, and data were compared for the years before and after the shift in legislation, both nationally, for each of the three major urban regions, and for the rest of the country. Comparisons were made with respect to concurrent mental health comorbidities, age and gender. Results The number of out-patient gambling disorder diagnoses increased over time, but without any significant step changes around the shift in legislation. Over time, patients were younger, became more likely to have gambling disorder as their primary diagnosis, and less likely to have mental health comorbidities, whereas gender distribution did not change. Among the smaller group of patients diagnosed in in-patient settings, mental health comorbidity increased over time. Despite gradual changes over time, no changes in demographics were seen around the actual shift in legislation, although the psychiatric comorbidity appeared to increase after this change. Conclusion After the introduction of gambling disorder in the responsibility of social services and health care settings in Sweden, the number of patients diagnosed with gambling disorder increased only modestly. Likely, further implementation of gambling disorder treatment is required in the health care services. Also, longer longitudinal studies are needed in order to understand to what extent patients not seeking health care treatment are received by municipal social services or remain outside the treatment system.